Ethnobotanical study of indigenous plants used by local people of Agusan del Sur, Philippines - Arquion, Rose D.; Galanida, Cesario C.; Villamor, Brenda; Aguilar, Henry T. (Asia Pacific Higher Education Research Journal (APHERJ), 2015)
Medicinal and wild edible plants are important for human existence. This study aimed to investigate medicinal uses of indigenous plants to human and to document wild edible plants (WEP). Ethnobotanical data were obtained from 493 informants using semi-structured interviews and field observations done in 32 communities. The study documented 126 species of medicinal plants belonging to 57 families and 105 genera. Herbs were largely utilized and prepared mostly by decoction, extraction, and infusion to cure human diseases/ailments. The largest number of taxa of medicinal plants came from Families of Gramineae and, Lamiaceae (7), Euphorbiaceae (6), Liliaceae, Asteraceae, Moraceae and, Malvaceae (5). Some documented 53 species of wild edible plants belong to 46 families mostly utilized as vegetables for food and sources of income. The commonly used wild edible plants belong to Family Convolvulaceae, Musaceae, and Arecaceae. Documenting these indigenous plants and associated ethnobotanical knowledge can be used as basis for developing management plan for conservation and sustainable use.